The Qur’an and the Earth: Qur’anic Reception Among Pesantren Residents toward Environmental Conservation - Karman, Karman; Yudiantara, Rully Agung; Muhyiddin, Asep (Universitas Islam Negeri Mataram, 2025)
Interactions with the Quran have led to a variety of interpretations. Some individuals approach the Quran from a theological standpoint, evaluating the accuracy of their understanding using established methods. In contrast, others take a more humanistic approach, incorporating Quranic teachings into daily life without being constrained by rigid methodologies. This study aims to investigate how residents of Pondok Pesantren Biharul Ulum Agroecology (PPBUA) in Cisarua, Bogor, receive and apply Quranic teachings in the context of environmental conservation. Using a qualitative-ethnographic approach, data were gathered through observation, interviews, and documentation. Grounded in reception theory, the findings reveal that PPBUA's environmental initiatives effectively combine Quranic principles with local wisdom, motivating both the community and students (santri) to view conservation as a form of worship. Through initiatives such as reforestation and organic farming, PPBUA fosters sustainability. By merging Quranic values with traditional practices, the institution offers a comprehensive approach that integrates spiritual, social, and ecological dimensions to create lasting solutions.